COMPARATIVE EVALUATION OF NUTRITIONAL STATUS AND LIFESTYLE OF DOCTORS AND NURSES WORKING IN A LOCAL PUBLIC HOSPITAL - TEHREEM , B; KAUSER , H; PARVEEN , R (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to compare doctors’ and nurses’ nutritional status and lifestyle working in a local hospital. The prospective study was conducted in DHQ Hospital Muzaffargarh. The study was conducted on 60 participants (30 doctors, 30 nurses).To conduct this study, a questionnaire was prepared and distributed. There were questions on weight, height, waist circumference, hip circumference, and BMI in addition to the standard demographic information (age, gender, parental status, income, and education). Questions on eating habits, supplement usage, digestive health, exercise, stress, and other aspects of lifestyle and diet, as well as their current nutritional status, were included in the survey. 2.0 doctors were underweight because their BMI was less than 18.5. Sixteen doctors and 22 nurses were healthy because their BMI was 18.5 - 14.97.8; doctors and 5 nurses were overweight because their BMI was 25.5 - 29.59. Four doctors and 3 nurses were obese because their BMI was 30.77 - 38.41. All variables showed no statistically significant variation in both groups except for waist circumference (p-value=0.053) and height (p-value=0.05). The pattern of exercise between both groups was not significantly different. There is no difference in the nutritional status and lifestyle of doctors and nurses.